The long-run relationship between trade and population health: evidence from five decades - Dierk Herzer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In recent years, the increase in international trade has sparked a debate about the impact of international trade on population health. To date, however, there has been very little econometric research on the relationship between these two variables. This paper examines the long-run relationship between trade openness and population health for a sample of 74 countries over five decades, from 1960 to 2010. Using panel time-series techniques, it is shown that international trade in general has a robust positive long-run effect on health, as measured by life expectancy and infant mortality. This effect tends to be greater in countries with lower development levels, higher taxes on income, profits, and capital gains, and less restrictive business and labor market regulations. The results also show that long-run causality runs in both directions, suggesting that increased trade is both a consequence and a cause of increased life expectancy.
Keywords: O11; F40; I12; 330